EchoNavigator® technology facilitates transapical mitral paravalvular leak closure: a case report. Issue 6 (5th June 2021) - Buzaev, Igor Vyacheslavovich; Khalikova, Gulchachak; Plechev, Vladimir Vyacheslavovich; Onorato, Eustaquio Maria
Abstract: Background: Catheter-based closure has emerged as a less invasive alternative to surgery in high-risk patients with paravalvular leak (PVL) and clinically significant regurgitation with feasibility and efficacy demonstrated in multiple studies. Case summary: A 72-year-old female with a past history of long-standing rheumatic heart disease underwent mechanical mitral valve replacement in 2008. Ten years later, redo surgery was performed due to a worsening mitral PVL and the leakage was closed by direct pledget-supported sutures, preserving the mechanical valve. She was recently admitted again for haemolytic anaemia and congestive heart failure (New York Heart Association Classes III–IV) due to a recurrent mitral PVL. We report our initial clinical experience using a novel software solution (EchoNavigator ® -system) for intuitive guidance during a catheter-based transapical mitral PVL closure. Discussion: Transapical mitral PVL closure with a specifically designed device demonstrated in our case to be a better option than redo surgery. Recently introduced fusion imaging modalities enhanced visualization of soft tissue anatomy and device location improving enormously the results of this challenging intervention.